Aerodynamic principles of flight vehicles - Panaras, A. G. (Library of flight., 2012)
This book examines the fundamentals of vortices and shock waves, aerodynamic estimation of lift and drag, airfoil theory, boundary layer control, and high-speed, high-temperature flow. Individual chapters address vortices in aerodynamics, transonic and supersonic flows, transonic/supersonic aircraft configurations, and high-supersonic/hypersonic flows, beginning with definitions and historical data, and then describing present-day status and current research challenges. Emphasis is given to flow control, the evolution of flight vehicle shapes as flight speed has increased, and discoveries that enabled breakthrough developments in flight. The book examines why various equations and technologies were developed; explains major contributors in areas such as vortices and aircraft wakes, drag buildup, sonic boom, and shock wave/boundary layer interactions, among others; and helps readers apply concepts from the material to their own projects. This resource is for both aeronautical students and professionals. --